2015
DOI: 10.1155/2015/756849
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Self-Efficacy and Psychosocial Care in Adolescents with Epilepsy

Abstract: Introduction. Studies about epilepsy are more associated with physiological aspects and drug therapy and far too little attention has been paid to psychological and social care, especially in teens. Hence, the present study aimed to assess relationship between self-efficacy and psychosocial care in adolescents with epilepsy. Methods. A cross-sectional association study was conducted on 74 consecutive adolescents aged 10 to 18 years with general attacks of epilepsy referred to Pediatric Neurology Clinics affili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“… 52 Supporting the potential utility of this resource, a recent study of adolescent PLWE found that easy-to-understand information about their illness was directly associated with higher self-efficacy. 52 …”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“… 52 Supporting the potential utility of this resource, a recent study of adolescent PLWE found that easy-to-understand information about their illness was directly associated with higher self-efficacy. 52 …”
Section: Discussionmentioning
confidence: 96%
“…In order to help reduce the stigma burden of epilepsy, healthcare providers should provide written and web-based educational materials that are highly readable and easily understood for people at all reading levels. 52 Supporting the potential utility of this resource, a recent study of adolescent PLWE found that easy-to-understand information about their illness was directly associated with higher self-efficacy. 52 Additionally, self-management programs that target both epilepsy and mental illness have the potential to provide adaptive methods for managing both illnesses and reduce depressive symptoms.…”
Section: Jcnmentioning
confidence: 96%
See 1 more Smart Citation
“…Moreover, both receiving care and extending care competencies might also satisfy the need for competence of adolescents. Appropriate care from others can increase self-efficacy -an assurance that a person can achieve his desired goal (Akbarbegloo et al 2015;Wang et al 2015). Similarly, helping others will improve how adolescents see themselves and value their contribution to the lives of others.…”
Section: Care Competencies and Well-being Of Adolescentsmentioning
confidence: 99%
“…pilepsy is a chronic neurological disorder that imposes many costs on individuals and society. In Iran, epilepsy is prevalent in 1.2 to 4 individuals per 1,000 people (Akbarbegloo et al 2015). People with epilepsy have limited information on their disease and thus, are poorly adapted to their conditions (Edward et al 2015).…”
Section: Introductionmentioning
confidence: 99%